Research on Key Technologies of Power System Automation Application under Smart Grid. Issue 4 (May 2020) - Zhang, Kexin; Tan, Long; Chen, Shiyu; Han, Siwei; Zhang, Dewen; Xu, Minhu
Abstract: With the continuous development of the scale of the power grid and the advancement of the integrated mode of regulation and control, the amount of real-time monitoring information in the power grid system has grown rapidly today, which has imposed a great burden on all levels of dispatch monitoring. The old alarm function of the power dispatching automation system has been unable to better meet the needs of efficient monitoring. Therefore, it is necessary to brush, analyse, process and summarize the alarm information of each link in the monitoring business, so as to improve the overall operation status of the power grid. Awareness and processing speed of abnormal faults. Based on this, this paper discusses and studies the smart alarms of the smart grid, analyses the overall architecture, and analyses several smart alarm technologies used in the smart grid system on this basis, with a view to the subsequent development of smart grids and alarms the technical research provides a theoretical reference.